Shear strength characteristics of muddy interlayers with different water contents and particle size distributions - Zumei Zha; Linwei Li; Yiping Wu; Fasheng Miao; Xiqiong Xiang; Dewu Liao; Zhengchao Wu; Yang Xue (PLoS ONE, 2026)
As a common weak structural plane, muddy interlayers often govern the stability of consequent bedding rock slopes (CBRSs). This study investigated the influence of water content (WC) and particle size distribution (PSD) on the shear strength characteristics of muddy interlayers in CBRSs. A series of CUTS tests was conducted to investigate the strength properties of remolded soil samples for muddy interlayers under WC and PSD conditions, and the maximum information coefficient (MIC) was used to evaluate the effects. The results revealed that under constant PSD, cohesion initially increased, subsequently decreased, and ultimately stabilized with increasing WC, whereas the internal friction angle (φ) consistently reduced. Under constant WC, increasing the proportion of soil particles (2–4 mm) from 0% to 40% reduced cohesion but increased φ. When the PSD changes, the coefficient of curvature ( C c ) positively affects cohesion but increases φ, whereas increasing the coefficient of uniformity ( C u ) has the opposite effect. MIC analysis revealed that changes in shear strength parameters due to variations in C c and C u were far greater than those caused by WC, highlighting the dominant role of PSD in controlling shear strength. These findings provide valuable insights for assessing the stability of rock slopes with muddy interlayers of similar compositions.